Ecological principles of agriculture - Powers, Laura E; Mc Sorley, Robert ([Africa] Delmar, 2000)
Ecological principles of agriculture will help in understanding the ecological principles operating in any agricultural system. Everyone will findit invaluable as a general overview of ecological principles especially as they relate to agricultural practi
Keywords: Agricultural ecology; Agriculture